La reposición de la fertilidad en la primera oleada de la transición socioecológica en la España Mediterránea. Andalucía Siglos XVIII-XX - González de Molina, Manuel (2012)
The transition from agriculture based on solar energy towards an industrial one in-volved great impacts, and usually has been study in terms of cropland distribution and changes in population. However, studies on the role of nutrient balance on the socio-ecological transition are scarce, despite that the replenishment of soil fertility was a critical factor for the long-term stability of the harvests, and this is especially true for Mediterranean region where manure vailability was low. In this study, the role of nutrient removal on that transition was evaluated in the inland Mediterranean region of south Spain between 1750 to 1900. Changes in cropland distribution, population, manure availability and demand, and cropland-nutrient balance and aggregated nutrient balance were performed. Data suggest that agriculture development at 1750 period was limited by manpower. Manure availability was higher than demanded and nitrogen balances were positive and slightly negative for phosphorus and potassium. During the 19th Century, population increased whereas livestock size, and manure availability, dropped. Nutrients balances become negative indicating that, during the 19th Century, crops productivity was based on soil mining. The territorial imbalance and marked soil mining were major reasons behind the turn of the century crisis, leading to the agrarian socio-ecological transition.